Development of chloroplast genome library for DNA tracking and conservation of endangered Aquilaria species native to Malaysia - Hishamuddin, Muhammad Syahmi (2022)
Aquilaria Lam., species [Aquilaria beccariana Tiegh., (gaharu buaya), Aquilaria crassna Pierre ex Lecomte, (gaharu), Aquilaria hirta Ridl., (chandan bulu), Aquilaria malaccensis Lam., (ching karas), Aquilaria microcarpa Baill., (gaharu putih), Aquilaria rostrata Ridl., (candan gunung), Aquilaria sinensis (gaharu) and Aquilaria subintegra Ding Hou, (gaharu)] is a naturally distributed in the Indomalesian region and are protected against over-exploitation. Aquilaria is highly prized for its unique scented resin, agarwood, which is often the subject of unlawful trade activities. Survival of the tree is heavily threatened by destructive harvesting and agarwood poaching, leading to its protection under the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Ambiguous species delimitation and limited genetic information within Aquilaria are among the impediments to conservation efforts. In this study, a comparative analysis was performed on eight Aquilaria species complete chloroplast (cp) genomes, of which seven were newly sequenced using Illumina HiSeq X Ten platform followed by de novo assembly. All Aquilaria species utilised in this study were collected during fieldwork and the Aquilaria germplasm of Forest Research Institute of Malaysia (FRIM), and grown in the greenhouse of the Faculty of Forestry and Environment, Universiti Putra Malaysia. All Aquilaria species have been authenticated by experts. To conduct comparative cp genome analysis, the sequences of all eight Aquilaria cp genomes were aligned using MAFFT v7 and then imported into DnaSP v5.10.1 to determine nucleotide diversity in the total genome, LSC, SSC, and IR regions. The boundaries between the IR and SC regions were manually examined to determine the differences in length variation between Aquilaria cp genomes. Aquilaria cp genomes possess a typical quadripartite structure including gene order and genomic structure. The length of each of the cp genome is about 174 kbp and encoded between 89 and 92 proteins, 38 tRNAs, and 8 rRNAs, with 27 duplicated in the IR (inverted repeat) region. Besides, 832 repeats (forward, reverse, palindrome and complement repeats) and nine highly variable regions (HVR) were also identified. The phylogenetic analysis performed using Maximum likelihood (ML) and Bayesian inference (BI) suggests that the topology structure of Aquilaria cp genomes were well presented with strong support values based on the cp genomes data set and matches their geographic distribution pattern. Five of the nine HVR (matK-rps16, ndhF-rpl32, psbJ-petA, trnD, and trnT-trnL) were selected based on a cut off value of >0.01. These regions were further analyzed using the neighbor-joining (NJ) method to assess their ability at discriminating the eight species. Coupled with in silico primer design, two potential barcoding regions, psbJ-petA and trnT-trnL, were identified. Their strengths in species delimitation were evaluated individually and in combination, via DNA barcoding analysis. The results showed that the combined dataset, psbJ-petA+trnT-trnL, effectively resolved members of the genus Aquilaria by clustering all species into their respective clades. In addition, this study show great potential for agarwood identification that the newly proposed DNA barcode was capable at identifying the species of origin of six commercial agarwood samples that were included as unknown samples. Such achievement offers a new technical advancement, useful in the combat against illicit agarwood trades and in assisting the conservation of these valuable species in natural populations. The identification of simple sequence repeats (SSR) across complete cp genome sequences from eight Aquilaria species has never been reported before. Perhaps because developing these genetic are regarded as laborious and expensive. To overcome this issue, the current work also aims to find SSRs in Aquilaria cp genomes using silico methods. For identification of the simple sequence repeats (SSRs), MISA PERL script which had a repeat length of 12 for mononucleotides (mono-), 6 for dinucleotides (di-), 4 for trinucleotides (tri-), 3 for tetranucleotides (tetra-), pentanucleotides (penta-), and hexanucleotides (hexa-), respectively, along with frequency were utilized. From a total of 312 SSRs that were discovered, merely 50 (16%) were found localized within the coding region while the majority (84%) were within the intergenic regions, with an average of one SSR per 4.5 kb. The mean length of the SSRs were 11.63 bp. Mono- repeats were the predominant motifs (29.2%), followed by tetra- (28.8%), di- (20.5%), tri- (19.9%), and penta- (1.6%). Whereas the most recurring motifs were A/T (97.8%) for mono-, AT/AT (87.5%) for di-, AAT/ATT (48.4%) for tri-, and AAAT/ATTT (45.6%) for tetra-. GO analysis using the REVIGO software identified four molecular functions, six biological processes and three cellular components. In conclusion, findings of this SSR offer a scientific foundation for future phylogenetics, evolutionary genetics, diversity studies and breeding programs on Aquilaria species.